Genetic risk factors for vascular aging: molecular mechanisms, polymorphism of candidate genes and gene networks - A. A. Slepukhina; E. M. Zelenskaya; G. I. Lifshits (Российский кардиологический журнал, 2019)
Age is considered an independent and primary risk factor in the development of cardiovascular disease. Aging of vascular cells induces complex changes in the structure and functions of the vasculature. The article discusses a number of molecular genetic mechanisms involved in the pathogenesis of vascular aging: cell and mitochondrial dysfunction, endothelial dysfunction, depletion of the progenitor cell pool, shortening and damage to telomeres, chronic inflammation, oxidative stress, and dysregulation of vascular tone. There is more and more evidence of cross-involvement in the vascular aging processes of candidate genes (such as ACE, SIRT1, TERC, FOXO1, FOXO3, APOE, NOS3) associated with life expectancy and cardiovascular diseases. For 26 genes involved in the presented molecular mechanisms of vascular aging, sites of functional polymorphisms are given. Understanding the main pathophysiological changes caused by vascular aging makes it possible to choose a preventive strategy. Modern approaches for better predicting of genetic risk are discussed in conclusion using the example of visualization of vascular aging genes network.